The Application of the Jigsaw Cooperative Learning Model to Improve Student Learning Outcomes in Class V Thematic Learning - Nurhaedah, Nurhaedah; Hermuttaqien, Bhakti Prima Findiga; Salsabila, Lale Ziyadati Rahma (Program Studi PGSD FIP UNM, 2023)
This study aims to describe learning outcomes in thematic learning for Class V SDN Borongkanang Kec. Bontonompo Kab. Gowa. The focus of this research is the application of the Jigsaw Cooperative learning model and student learning outcomes in thematic learning. The approach used in this research is a qualitative approach with this type research, namely Classroom Action Research which consists of 2 cycles and each cycle consists of 2 meetings. The data analysis used is descriptive qualitative analysis. The results of the study show that there is an increase in the quality of learning, both in teacher-teaching activities and student learning activities as well as student learning outcomes. The results of observations of teacher teaching activities and student learning activities in cycle I were still in the poor category, while in cycle II there was an increase in the good category. The results showed that there was an increase in student learning outcomes in thematic learning through the application of the Jigsaw cooperative learning model. The test results of cycle I mean that the average student score has not reached the KKM that has been determined, while in cycle II there has been an increase where the average student score has met the KKM that has been determined. The conclusion of this study is that the application of the Jigsaw Cooperative learning model can improve student learning outcomes in thematic learning class V SDN Borongkanang Kec. Bontonompo Kab. Gowa.